(untitled) (Vietnam Journal of Community Medicine, 2026)
Research Objectives: To describe the drug utilization structure and analyze the drug formulary using the ABC/VEN method at Hai Duong Medical Technical University Hospital in 2023. Study materials: A total of 350 medicines used at Hai Duong Medical Technical University Hospital from January 1, 2023 to December 31, 2023, including 329 modern medicines and 21 traditional medicines. Research Methods: A retrospective cross-sectional descriptive study. Results: A total of 350 drug items were utilized, corresponding to a total expenditure of VND 8,700.1 million, mainly concentrated in four therapeutic groups: hormones and endocrine system drugs; antiparasitic and anti-infective agents; cardiovascular drugs; and gastrointestinal drugs.The majority of the drugs used were domestically manufactured, accounting for 232 items (66%) and 58% of the total drug utilization value. Oral medications represented the highest proportion, accounting for 53% of all items and 68% of the total utilization value. Single-component drugs predominated, with 272 items (82.7%) valued at VND 6,413.8 million (79%). Within the therapeutic groups of hormones and endocrine system drugs, as well as antiparasitic agents, drug utilization was concentrated in 10 active ingredients comprising 35 items, accounting for 27% of total use. Regarding the ABC analysis, class A drugs accounted for 75% of total drug utilization value, while classes B and C accounted for 15% and 10%, respectively. The ABC/VEN analysis demonstrated that Group I (AV, AE, AN, BV, and CV) included 75 high-value drug items, representing 76.46% of total utilization value, which therefore require strict monitoring during procurement, storage, preservation, and use. Eight drugs belonging to the AN and BN categories should have their utilization restricted. The CN group accounted for only 0.32% of total utilization value and consisted of non-essential drugs that may be considered for removal from the formulary.Conclusion: The hospital formulary was diverse and adequately met the needs of medical examination and treatment at the hospital. The study provided useful evidence for the Drug and Therapeutics Committee and the Department of Pharmacy to identify irrational issues in drug supply management, optimize resource allocation, and prevent stock-outs in the hospital pharmacy. Priority should be given to closely monitoring the use of Group I drugs (AV, AE, AN, BV, and CV), with regular surveillance of stock levels because these are considered essential medicines. In terms of drug management, the findings support prioritizing control of drugs according to their level of importance, particularly class A drugs. The use of AN and BN drugs should be limited to reduce unnecessary expenditure, while CN drugs may be removed from the formulary.